Asiatic Acid Induces Mitochondrial Apoptosis via Inhibition of JAK2/STAT3 Signalling Pathway in Human Osteosarcoma - Yan, B. F; Chen, X; Liu, J; Liu, S. J; Zhang, J. Z; Zeng, Q. Q; Duan, J. A (Folia biologica (Praha), 2021)
Osteosarcoma (OS), a severe malignant bone tumour, usually occurs in adolescents and children and has a poor prognosis. Asiatic acid (AA), an active component isolated from Centella asiatica (L.) Urb., exhibits appreciable anti-oxidant and anti-tumour activities. So far, the effects and underlying mechanisms of AA against OS have not been clarified. Here, we explored the anti-tumour effects of AA against human OS and the involved mechanism mediating its actions. To evaluate effects of AA on the cell proliferation of human OS cells, cell viability and colony formation assays were performed. Flow cytometry was used to evaluate apoptosis in OS cells exposed to AA and mitochondrial membrane potential. Western blotting and RT-PCR were applied to determine expression of the relevant proteins and their mRNA levels. Our explorations showed that AA inhibits proliferation of human OS cells in a concentration- and time-dependent manner, and induces apoptosis of OS cells by the intrinsic (mitochondrial) pathway. Importantly, we found that inhibition of the AA-induced phosphorylation of JAK2/STAT3 signalling molecules and the decrease in MCL-1 contributed to the anti-tumour efficacy of AA. Collectively, our results suggest that AA could evoke mitochondrial- induced apoptosis in human OS cells by suppression of the JAK2/STAT3 pathway and MCL-1 expression. These results strongly demonstrate that AA could be a potential anti-tumour agent for OS treatment.
Keywords: pentacyklické triterpeny; STAT3 Transcription Factor; Adolescent; Humans; proliferace buněk; apoptóza; Pentacyclic Triterpenes; lidé; Osteosarcoma; transkripční faktor STAT3; Janus Kinase 2; Janus kinasa 2; Cell Line, Tumor; osteosarkom; mladiství; nádorové buněčné linie; Apoptosis; Cell Proliferation